GE_GERICHTE C/6153/2012 vom 16. April 2013 - GE Cour de justice (2013)
DIVORCE; MESURE PROVISIONNELLE; MODIFICATION DE LA DEMANDE; DROIT DE GARDE; VISITE ; CURATELLE | CPC.276.1. CPC.299. CC.273.1. CC.315.1. CC.307.3